Pengaruh Bridging Exercise dan Stretching Terhadap Lama Waktu Aktivitas Silasana di Balai Banjar Megati Kaja Tabanan Bali - Bayu Suryawan, Dewa Made, Totok Budi Santoso , S.Fis , MPH, Wahyuni, SSt.FT.M.Kes (2015)
Background: Silana activity is sitting position with crossed legs that usually called bersila. This activity usually used by the members of BalaiBanjarMegatiKaja for meeting and also social activity. The result of study was finding 28 from 54 subjects felt hurt in their back pain, buttock and tingling in the limbs, thereforedid thesilasana with long time was difficult. The subjects which are 28 members who comply inclusion criterion which are 10 respondents. Objective: To know whether or not bridging exercise and stretching influence the duration activity of silasana. Methods: The previous research is used in this present study as pre-eksperiment (one group pretest-posttest design), with 10 subjects sample. By the instruments was use for measure the silasana activity. The other instruments was use pre and post wilxocon with probability value <0.05 Ho was rejected. Result: The bridging exercise and stretching is influence the silanaactivity after the researcher applied the statistic test with wilxocon that finally result was getting the significance value (p)= 0.008. Conclusion: There is an influence of bridging exercise and stretching for duration ofsilasana activity in Banjar Megati Kaja. Keywords:Bridging exercise and streaching, duration of silasana activity in BalaiBanjarMegatiKaja.